Effect of environmental constraints on multi-segment coordination patterns during the tennis service in expert performers - Shafizadeh, M.; Bonner, S.; Fraser, J.; Barnes, A. (Journal of Sports Sciences, 2019)
The aims of this study were to examine the effect of different environmental constraints on kinematic multi-segment coordination patterns during the service and its coordination with service time variability. Ten expert tennis players (Age: 34.1 ± 5.3) volunteered to take part in this study. Participants served 30 times in 3 different conditions: control, target and opposition. The order of conditions was counterbalanced between participants. A wireless 3D motion capture system (STT Co, Spain) was used to measure 7 joint motions, with a 17 degrees of freedom biomechanical model created to capture the entire service action. Results of the principal component analysis showed that 4 synergies were created; however, their roles were changed relative to the perception of the environment. The results of repeated-measures analysis of variance did not show any significant difference on total variance and individual principal components between conditions; however, one synergy pattern significantly predicted the service time variability in both control and opposition conditions. In conclusion, the findings demonstrated that expert performers reduce the joint dimensionality by creating functional synergies in different phases of service and adapt the service action according to the perception of the environment.